Assessing Outcome in Interhospital Infant Transport: The Transport Risk Index of Physiologic Stability Score at Admission - Lucas da Silva, Paulo Sérgio; Euzébio de Aguiar, Vânia; Reis, Maria Eunice (American Journal of Perinatology, 2012)
Objective To evaluate the performance of the Transport Risk Index of Physiologic Stability (TRIPS) score at admission for early mortality prediction.Methods The study included all consecutive outborn infants admitted to a single neonatal intensive care unit (NICU) over a 3-year period. The data collected included demographic variables, 7-day NICU mortality, and severe (≥ grade 3) intraventricular hemorrhage (IVH), TRIPS score at admission, and Score for Neonatal Acute Physiology II (SNAP-II) and SNAP-Perinatal Extension-II (SNAPPE-II) scores.Results A total of 175 neonates were enrolled. TRIPS at admission discriminated 7-day mortality from survival with a receiver operating characteristic (ROC) area of 0.80, and predictive performance of TRIPS for severe IVH showed a ROC area of 0.67. The TRIPS had good calibration for all strata (p = 0.49). For gestational age (GA) >32 weeks, the area under the curve (AUC) for TRIPS was 0.71, whereas the AUC for GA ≤32 weeks was 0.99 for 7-day mortality. Predictive performance of TRIPS for 7-day mortality was similar to that of SNAP-II and SNAPPE-II.Conclusion TRIPS score at admission had a good performance to discriminate high-risk patients for 7-day mortality, mainly infants with GA ≤32 weeks. TRIPS might be a useful triage tool if applied at the time of first contact with a transport service.
Keywords: illness severity; infants; neonatal mortality; risk assessment; transport